Outcomes of patients with solid tumour malignancies treated with first-line immuno-oncology agents who do not meet eligibility criteria for clinical trials. (July 2021) - Gan, Chun L.; Stukalin, Igor; Meyers, Daniel E.; Dudani, Shaan; Grosjean, Heidi A.I.; Dolter, Samantha; Ewanchuk, Benjamin W.; Goutam, Siddhartha; Sander, Michael; Wells, Connor; Pabani, Aliyah; Cheng, Tina; et al.
Abstract: Background: Immuno-oncology (IO)–based therapies have been approved based on randomised clinical trials, yet a significant proportion of real-world patients are not represented in these trials. We sought to compare the outcomes of trial-ineligible vs. -eligible patients with advanced solid tumours treated with first-line (1L) IO therapy. Patients and methods: Using the International Metastatic Renal Cell Carcinoma (RCC) Database Consortium and the Alberta Immunotherapy Database, patients with advanced RCC, non–small-cell lung cancer (NSCLC) or melanoma treated with 1L PD-(L)1 inhibition–based therapy were included. Trial eligibility was retrospectively determined as per commonly used exclusion criteria. The outcomes of interest were overall survival (OS), overall response rate (ORR), treatment duration (TD) and time to next treatment (TTNT). Results: A total of 395 of 1241 (32%) patients were deemed trial-ineligible. The main reasons for ineligibility based on preselected exclusion criteria were Karnofsky performance status <70%/Eastern Cooperative Oncology Group performance status >1 (40%, 158 of 395), brain metastases (32%, 126 of 395), haemoglobin < 9 g/dL (16%, 63 of 395) and estimated glomerular filtration rate <40 mL/min (15%, 61 of 395). Between the ineligible vs. eligible groups, the median OS, ORR, median TD and median TTNT were 10.2 vs. 39.7 months (p < 0.01), 36% vs. 47% (p < 0.01), 2.7 vs. 6.9 months (p < 0.01) and 6.0 vs. 16.8 months (p < 0.01), respectively. Subgroup analyses showed statistically significant inferior OS, TD and TTNT for trial-ineligible vs. -eligible patients across all tumour types. Adjusted hazard ratios for death in RCC, NSCLC and melanoma were 1.84 (95% confidence interval [CI] 1.22–2.77), 2.21 (95% CI 1.58–3.11) and 1.82 (95% CI 1.21–2.74), respectively.. Conclusions: Thirty-two percent of real-world patients treated with contemporary 1L IO-based therapies were ineligible for clinical trials. Although one-third of the trial-ineligible patients responded to treatment, the overall trial-ineligible population had inferior outcomes than trial-eligible patients. These data may guide patient counselling and temper expectations of benefit. Highlights: The clinical effectiveness of immuno-oncology (IO) agents in the trial-ineligible cancer population is unclear. A total of 1241 patients with RCC, NSCLC and melanoma treated with first-line IO therapy were studied. 32% of real-world patients were ineligible for IO clinical trials. These patients had inferior outcomes compared with trial-eligible patients. These data may temper expectations of treatment benefit in the real-world.